INTEGRATION OF FULL-TIME AND DISTANCE LEARNING IN PEDAGOGICAL POSTGRADUATE TRAINING SYSTEM (Journal of Information Technologies in Education (ITE), 2010)
The article deals with advantages and disadvantages of distance learning. The author analyses the features of elementary school teacher's training in the system of postgraduate teacher's training regarding full-time and distance learning.
Keywords: distance learning; full-time and distance learning; informatively of communication technologies; pedagogical postgraduate education training system